There will be blood… a complete audit cycle. (13th March 2011) - Pericleous, M; Murray, C; Hamilton, M; Epstein, O; Negus, R; O'Beirne, J
Abstract : Introduction: Acute upper GI bleeding (AUGIB) has 7% new-admission mortality.1 The authors studied the management of patients with AUGIB at the Royal Free Hospital (RFH), London. The aim was to compare our performance to the standard practice as set by SIGN guidelines, 2 and determine ways of improving delivery of care. Methods: The authors randomly selected 15% of patients3 who presented with haematemesis, melaena, or both, and had an oesophagogastroduodenoscopy (OGD) in April to October 2009. Acute assessment and management were matched to the SIGN guidelines (audit standard). The authors developed local guidelines, and presented their findings in various forums including the Grand Round and clinical governance meetings. The authors collaborated with the British Medical Journal (BMJ) and Cerner Millennium electronic patient record system to create an electronic Action Set for the assessment and emergency management of adult patients presenting with AUGIB. The Action Set went live in April 2010 and the authors reaudited using the same standard and target. Results: Prior to the introduction of the Action Set 0% of doctors calculated the pre-OGD Rockall score. This increased to 33% following implementation (figure 1 ). The authors also noticed an increase from 25% to 100% of those patients who were admitted with a pre-OGD Rockall score of 'zero' and were correctly discharged with follow-up plans (figure 2). 34% of patients were correctly identified as not appropriate to receive a proton pump inhibitor (PPI) prior to OGD as compared to 15% previously. Inappropriate use of PPIs after OGD was reduced from 96% to 75%. Incorrect administration of intravenous PPI infusions dropped from 100% to 33%. Conclusion: Several areas of deviation from the guidelines were identified. The authors emphasised the usefulness of pre/full-Rockall scores as a risk-stratifying tool in order to determine potential discharges, create more beds and improve health economics for the Trust. Appropriate use of PPIs can reduce rebleeding rates, 4 improve mortality5 and reduce costs. The Action Set consists of a set of orders based on clinical evidence that can be used for the assessment and management of AUGIB. Local and SIGN guidelines and useful contacts/bleep numbers are incorporated in the workflow. The tool 'captures' patients with suspected AUGIB and records/time-stamps every event in the patient's journey. Tests and procedures are automatically ordered and auditable data is streamed, collected and analysed weekly. The Action Set includes e-prescribing and nurse ordering functionality. Even with minimal use the authors noticed improvements in several areas including guideline adherence, clinical outcomes and cost-cutting.